Growing Concerns on Antimicrobial Resistance – Past, Present, and Future Trends - Deepak Saxena; Richa Gwalani; Aarti Yadav; Ragini Shah (Indian Journal of Community Medicine)
Antimicrobial resistance [AMR] is a global problem that affects multiple domains including healthcare, agriculture, aquaculture, and many more. Every year, 700,000 people die from it. AMR is predicted to claim 10 million lives by 2050 if immediate action is not taken. Thus, to halt the spread of AMR it is important to understand what contributes to its emergence and transmission across borders and domains. The burden is disproportionately higher in Low middle income countries (LMICs) due to multiple factors such as environmental, social, healthcare, and cultural barriers. This review paper describes the comprehensive analysis of the past, present, and future trends in AMR, focusing on the complex interconnectedness of the factors contributing to this issue. Historical trends reveal antibiotic discoveries, resistance periods, resistance genes, and multidrug-resistant pathogens, providing insights into crisis evolution and the emergence of multidrug-resistant pathogens. The present trends reflect the current state of AMR in India and emphasize the negative consequences of AMR for clinical medicine and healthcare systems. It identifies the factors driving the global pandemic surge and examines current global and country-level policies and actions to mitigate its impact. The future trends anticipate the trajectories of AMR and discuss innovative approaches to combat resistance, including the exploration of alternative therapies and the implementation of stewardship programs. Thus, by synthesizing existing knowledge and identifying emerging gaps, this review paper presents a holistic perspective on the evolution of AMR.